Prognostic factors from squamous cell carcinoma of the hard palate, gingiva and upper alveolar ridge - Luan Nathiel Santana Kovalski; Virgilio Gonzalez Zanella; Luisa Comerlato Jardim; Bruna Barcelos Só; Fabio Muradás Girardi; Ricardo Gallicchio Kroef; Marinez Bizarro Barra; Vinicius Coelho Carrard; Manoela Domingues Martins; Marco Antonio Trevizani Martins (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: The purpose of this study was to evaluate the clinicodemographic characteristics and treatment protocol as prognostic factors in patients with oral squamous cell carcinoma (OSCC) of the hard palate, upper gingiva, and alveolar ridge (HPUGAR). This retrospective cohort study collected data of patients treated in two head and neck surgery departments in southern Brazil between 1999 and 2021. Information on clinicodemographic data, habits, site, size, clinical aspect, clinical staging, cervical metastasis, treatment, and survival was collected. Associations between independent variables and outcomes were assessed using Pearson's chi-square test and binary regression. Kaplan-Meier test was employed to compare the survival between the neck approaches. Forty-one patients were included; most were male (61%), with a mean age of 68.8 (± 13.9) years. The consumption of tobacco (p = 0.003) and alcohol (p = 0.02) was significantly higher in male than in female patients. The main clinical features observed in the study sample were lesions larger than 2 cm (48.7%), no cervical (90.2%), or distant metastasis (90.2%). Surgery alone was the main treatment approach (48.8%). The watch-and-wait strategy was adopted in 34 cases (83.0%), while elective neck dissection was applied in five (12.2%). Only two patients with cN0 disease (4.9%) presented with cervical metastasis at follow-up. Eight patients (12.2%) died of the disease. Clinicodemographic variables, habits, surgical margins, and histological subtype were not significantly associated with cervical metastasis or survival. Cervical metastasis (p = 0.004) was associated with poor survival. No difference was detected in survival between different neck approaches (p = 0.28). Cervical metastasis and local recurrence are negative prognostic factors for HPUGAR OSCC.